Health promotion in schools: the contribution of health professionals in seven West African countries - (:unkn) unknown (My University, 2023)
This comparative study aims to show how health professionals are involved in the medical follow-up of pupils in West Africa (Senegal, Mali, Côte d’Ivoire, Burkina Faso, Benin, Togo, Guinea). It is based on an analysis of school health policies and interviews with health and education professionals. School health services are present in all countries, and in most cases they are run by one or more health professionals.
Keywords: African Research